GROWTH AND PRODUCTION RESPONSE OF THE PLANT OF TELANG PLANTS TO GIVING DOSES OF NPK FERTILIZER AND PLANTING MEDIUM IN ROB AREA WITH FLOATING SYSTEMS - Satria Afigiatan, Arbina; Lestari, Dini; Rattanapun, Supot (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
The research to determine the application of NPK doses and types of planting media and their interactions on morphological characters and yield of Telang plant. The research was conducted in Denasri Wetan paddy field, Batang District, Batang Regency with an altitude of ± 3 m above sea level. The experimental design used Factorial Randomized Block Design (RBD) consisting of 2 factors with 3 repeats. The factors tried were the doses NPK (D) and planting media (M). The first factor was the doses NPK (D) consisting of a dose of 7,5 g/polybag (D1), a dose of 15 g/polybag (D2), and a dose of 22,5 g/polybag (D3). The second factor is the types of planting media (M) consisting of soil planting media (M0), soil + sand + rice musk (M1), soil + rice musk + manure (M2), and soil + sand + manure (M3). Data were analysed by the F test and continued with Least Significance Different (LSD) level 5%. Variable analysed were plant height (cm), leaf area (cm2), number of leaves (strands), number of branches (branches), longest root length (cm), root volume (ml), fresh flower weight (g), dry flower weight (g), number of flowers (piece), and time appearance of flowers (DAP). The results showed that the NPK doses were significant different and very significant different in the variable plant height, leaf area, longest root length, root volume, fresh flower weight, dry flower weight, and number of flowers whereas in other variables it was not significant different. The best NPK dose was achieved with a doses of 15 g/polybag (D2). The planting media had very significant different to all variables except the longest root length variable, which was not significant different. The best planting media is soil + rice husk + manure (M2). There was an interaction between the doses NPK and the planting media which was significant different for variable plant height and leave area and not significant different in other variable. The best interaction was achieved at a combination of dose NPK 15 g/polybag with planting media soil + rice husk + manure (D2M2).